Penggunaan Pendekatan Permainan Untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas 1 Sekolah Dasar - Jayadi, Iguk; Juaini, Muhamad; Ali, Muhamad (Universitas Hamzanwadi, 2024)
This research is motivated by the condition of students who experience delays in beginning reading in class I of Selangit State Elementary School. The focus of the research in this thesis is: 1) Beginning reading ability using the Game Approach for participants. 2) Teacher strategies in improving beginning reading ability through letter card media using the Game Approach for students. 3) Teacher strategies in improving beginning reading ability through word card media using the Game Approach for students. This research uses a qualitative approach and descriptive research type. The location of the research is at Selangit State Elementary School. Data sources are obtained from two types, namely primary and secondary data sources. Data collection methods use interviews, observations, and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. While checking the validity of the data uses (1) extension of participation, (2) persistence, (3) triangulation. The results of the study: 1) The ability to read early using the Game Approach for students at SD Negeri Selangit, namely there are several students who are not yet fluent in reading, then the school has a policy or program to improve the reading ability of these students, namely by providing intensive guidance for reading the Literacy Program, reading corners in each class, 10 minutes of reading before learning begins and using the Game Approach used by grade I teachers because the application is easy and fun so that it helps children understand and master reading fluently. 2) The teacher's strategy in improving the ability to read early through letter card media using the Game Approach for students at SD Negeri Selangit, namely the letter card media is used to help develop children's memory at the early reading stage. With that, students will be able to explore finding new vocabulary and increasing their vocabulary. 3) The teacher's strategy in improving the ability to read early through word card media using the Game Approach for students at SD Negeri Selangit, namely the word card media is very suitable for grade 1 students because the word card media uses words.